Recent insights into the extraction, characterization, and bioactivities of chitin and chitosan from insects. (November 2020) - Mohan, Kannan; Ganesan, Abirami Ramu; Muralisankar, Thirunavukkarasu; Jayakumar, Rajarajeswaran; Sathishkumar, Palanivel; Uthayakumar, Venkatachalam; Chandirasekar, Ramachandran; Revathi, Nagarajan
Abstract: Background: Insects are a living resource used for human nutrition, medicine, and industry. Several potential sources of proteins, peptides, and biopolymers, such as silk, chitin, and chitosan are utilized in industry and for biotechnology applications. Chitosan is an amino-polysaccharide derivative of chitin that consists of linear amino polysaccharides with d -glucosamine and N-acetyl-d -glucosamine units. Currently, the chief commercial sources of chitin and chitosan are crustacean shells that accumulate as a major waste product from the marine food industry. Existing chitin resources have some natural challenges, including insufficient supplies, seasonal availability, and environmental pollution. As an alternative, insects could be utilized as unconventional but feasible sources of chitin and chitosan. Scope and approach: This review focuses on the recent sources of insect chitin and chitosan, particularly from the Lepidoptera, Coleoptera, Orthoptera, Hymenoptera, Diptera, Hemiptera, Dictyoptera, and Odonata orders. In addition, the extraction methods and physicochemical characteristics are discussed. Insect chitin and chitosan have numerous biological activities and could be used for food, biomedical, and industrial applications. Key findings and conclusions: Recently, the invasive and harmful effects of insect species causing severe damage in agricultural crops has led to great economic losses globally. These dangerous species serve as potential sources of chitin and are underutilized worldwide. The conclusion of the present study provides better insight into the conversion of insect waste-derived chitin into value-added products as an alternative chitin source to address food security related challenges. Graphical abstract: Image 1 Highlights: Extraction methods and structural characterization of chitin and chitosan from insects were summarised. Biological activities of the insect chitin and chitosan were briefly discussed. New perspectives for the future work of these polysaccharides were suggested.